Proceso de modificación de sólidos en el aceite de palma (Elaeis guineensis jaquet) mediante la interesterificación con adición de látex de babaco - Manobanda Manotoa, José Luis (2011)
This research aims to evaluate the overall solids content of palm oil by interesterification using latex babaco. In America, Ecuador is the second largest producer of African palm, the fourth largest exporter of palm oil and the second consumer to industrial level. This vegetable oil obtained from the fruit mesocarp of Elaeis palm (E. guineensis), is considered the second most widely produced second only to soybean oil. Crude palm oil is rich source of vitamin A and have amounts of vitamin E. and applying appropriate modification techniques allows for a wide variety of products for the food industry, among which are the cooking oils, shortenings, margarine bases (vegetable fat substitute for butter in the kitchen) and for oil industry chemistry, raw materials for the manufacture of soap, metal soaps, candles and grease. This study was conducted in the laboratory of the company Epacem sa, located in the 7 ½ mile road-Quinindé Santo Domingo, Santo Domingo in the canton of the province of Santo Domingo de los Tsáchilas. The sample collection and preparation of palm oil and latex babaco was held at the Colorado Barrio Brisas del sector 2. We used an experimental design AxBxC with 8 treatments and 3 replications per treatment, which are subject to two levels of temperature (factor A), periods of time (factor B) and the percentages of latex: (factor C). Upon completion of all processing of palm oil change was performed proximal analysis of solids It recommended further research on the modification of fats and oils using enzymes of plant origin and that these would prevent the formation of trans fatty acids by taking into account the temperature 50 ºC, reaction time than 8 hours and a percentage of substrate or latex 0.33 %. After performing the respective analysis of cost in the production of these products and because of the cost of enzyme production is $ 18.00 per pack 900g